Penggunaan metode sugesti imajinasi untuk meningkatkan keterampilan menulis pantun peserta didik kelas v sekolah dasar - Dewi Ayu Asari; Slamet Slamet; Joko Daryanto (Didaktika Dwija Indria, 2020)
This research has purpose to improve fifth grade student in writing pantun. Imagination of sugestion applyed to solve the problem. This research was done in Kerten 2 Elementary School in 2019/2020. This Research was a classroom action research. Students and fifth grade teacher of Kerten State Elementary School 2 is subject of this research. The result of  pantun writing test, observation, Interview and documentation as supporting data. Technique of collected data which used by the researcher are interviewing,observation in class and also documentation. Triagulation and content validity was technique for data validation. Interactive analysis model by Miles Huberman that used in this research for data analysis. The results of this study were the poetry writing skills of students using the imagination suggestion method increased with 81% of students scored above the minimum completeness criteria.